PENGARUH KEPUASAN DAN EFEKTIFITAS IKLAN PESAING TERHADAP KEINGINAN BERPINDAH DENGAN BIAYA PERALIHAN DAN PERILAKU MENCARI VARIASI SEBAGAI VARIABEL MODERASI PADA PENGGUNA KARTU PRA BAYAR GSM - Werdiasih, Rustina Dewi (JURNAL EKONOMI, 2014)
This study was conducted because of the differences in the results of previous research on the relationship between the customer satisfaction several research states that customer satisfaction negatively affect brand switching intention, whereas another study found results that a number of customers who express satisfaction still switch brands. This study is development from other research. Previous studies only examined a limited internal factors influence customers towards brand switching but that the study is also, analyzed the influence of competitors advertising effectiveness. Number of respondents 120 people. The purposive sampling method used in this research. Respondents who sought condition GSM Pre-paid card users in Cilacap at least 3 months, aged 17 to 60 years and often their change GSM prepaid card or use a different card brands. Analysis tools using Structural Equation Modelling.Hypothesis testing results as follows: Customer Satisfaction negative influence brand switching intention, switching costs has no effect on brand switching, switching costs no moderate the relationship between satisfaction and intention of brand switching, variety seeking behavior has no effect on brand switching intention, variety seeking behavior moderate the relation betwen satisfaction brand switching intentions, competitor advertising effectiveness has a positive influence on brand switching intention and variation seeking behavior moderate affect competitors' advertisements on brand switching intention.Keywords: Customer Satisfaction, Switching Costs, Variety Seeking Behavior, Competitive Ad Effectiveness, Brand Switching Intention.